Pengaruh Role Stressor Terhadap Komitmen Organisasi dengan Pemberdayaan Karyawan Sebagai Variabel Intervening - Abdul Khair Hakim; T. Juli Yanti; Muhammad Rusydi Hakim; Putri Permata Indah; Amri Ady; Nur M. Ridha Tarigan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of Role Stressor on organizational commitment with employee empowerment as an intervening variable on Cv. Kotama Shoes Medan. Data collection techniques used in this study were surveys and questionnaires. The population and samples used in this study were employees at Cv. Kotama Shoes Medan as many as 100 employees as the research sample. The data analysis technique used in this study is testing the validity and reliability of the data, classical assumption test, regression test, path analysis and the coefficient of determination. Some of the variables used in this study are role conflict, role ambiguity, role overload and employee empowerment. The role conflict variable has a negative and significant effect on commitment with a value of -0.532 and a significance value of 0.013, so hypothesis 1 is accepted. The variable role ambiguity has a negative and significant effect on commitment with a value of -0.525 and a significance value of 0.008, so hypothesis 2 is accepted. The role overload variable has a positive and significant effect on commitment with a value of 0.583 and a significance value of 0.036, so hypothesis 1 is rejected. Employee empowerment variable employee empowerment is not able to mediate the effect of role conflict, role ambiguity, and role overload on organizational commitment. This is evidenced by the t-count value of the role conflict variable of -0.1579 , role ambiguity of -1.0879, and the t-count value of role overload of 1.003 , this explains that the t-count value of each variable is smaller than t table of 1,983. This means that employee empowerment cannot mediate the effect of the independent variable on the dependent variable. Based on this statement, hypotheses 2, 5 and 6 are rejected.